In situ TEM observation of controlled growth of two-dimensional WS2 with vertically aligned layers and high-temperature stability. (January 2020) - Zhang, Yanan; Zhang, Zhi; Cheng, Yongfa; Cheng, Feng; Wang, Longfei; Liu, Nishuang; Li, Luying; Su, Jun; Gao, Yihua
Abstract: Layered transition metal dichalcogenides with vertically aligned morphology show great potentials in energy conversion and storage due to the high density of exposed edge sites which have enhanced electrochemical reactivity. In this letter, through in situ heating investigations in a transmission electron microscope, the controlled growth of vertically aligned WS2 with high-temperature stability has been achieved through the thermolysis of solid precursor K2 WS4 . It is found that the growth of vertically aligned WS2 layers employs hybrid growth modes, in which the growth of new WS2 slab is initiated at old ones from either the middle part or edge part. These vertically aligned WS2 layers show great stability at high temperature of 900 °C. Our detailed investigations and theoretical calculations indicate that potassium element in the solid precursor plays a critical role in the growth and evolution of vertically aligned WS2 . This method is also applicable to the controlled growth of vertically aligned MoS2 with high-temperature stability through the decomposition of K2 MoS4 . These findings pave a way for tailored design and fabrication of materials with optimized structure to achieve their superior properties. Graphical abstract: In situ TEM observation of controlled growth of vertically aligned WS2 layers. Image 1 Highlights: Controlled growth of vertically aligned WS2 layers has been achieved through the thermolysis of solid precursor K2 WS4 . In situ TEM observations indicate that the growth of vertically aligned WS2 layers employs hybrid growth modes. These vertically aligned WS2 layers show excellent stability even at high temperature of 900 °C. These results indicate that potassium element in precursor plays a critical role in the growth of vertically aligned WS2 .